Case Report: Thrombus aspiration and in situ thrombolysis via a Guidezilla guide extension catheter in a patient with high-risk pulmonary embolism - Ding, Jing-Wen; Jiang, Yu-Ang; Li, Peng; Xie, Hong-Xiang; Ding, Huai-Sheng (Frontiers in Cardiovascular Medicine, 2024)
Standard catheter-directed thrombolysis (CDT) and thrombus aspiration are considered potentially promising approaches for reopening the embolism-related pulmonary artery in patients with pulmonary embolism (PE) with high thrombotic burden and deteriorating hemodynamics, especially in those for whom systemic thrombolysis is contraindicated or has failed. However, the constrained accessibility of dedicated catheters has impeded the potential benefits of standard CDT in developing countries. The Guidezilla guide extension catheter (GEC) with a larger diameter and extended length is widely used in challenging coronary anatomy. Nevertheless, there have been few reports on the application of the Guidezilla GEC as a novel option for patients with massive PE when dedicated catheters and surgical thrombectomy are not available. In this case report, we demonstrated that thrombus aspiration and in situ thrombolysis through the Guidezilla GEC are applicable to patients with PE in whom systemic thrombolysis is contraindicated, resulting in successful reperfusion and positive clinical outcomes.